SERUM FT3, FT4,TSH AND PROTEINS IN CHILDREN WITH PROTEIN ENERGY MALNUTRITION. - SHAHEEN B; ISMAIL M HAJI; SUMA M B; AKILA P; SARFARAJ S (International Journal of Pharma and Bio Sciences, 2013)
Protein-energy malnutrition (PEM) is one of the important causes of under 5 morbidity and mortality in our country. The aim of this study was to assess the thyroid hormone levels and to correlate the levels with serum protein levels in the PEM patients with that of healthy controls. Serum thyroid hormones and serum proteins were measured in 30 protein energy malnourished children of different grades (I-IV).Serum levels of free tri-iodo thyronine (FT3),Free thyroxine (FT4) and thyroid stimulating hormone (TSH) were measured by chemiluminometric assay, serum total proteins by biuret method and serum albumin by BCG Dye method. The results were compared with 30 healthy, age and sex matched controls. There was a significant decrease in serum FT3, FT4 and TSH and serum total proteins in PEM patients, when compared to the control group. There was a significant positive correlation between serum thyroid hormones and serum albumin levels in PEM cases.